Distinguishing between basalts produced by endogenic volcanism and impact processes: A non-destructive method using quantitative petrography of lunar basaltic samples. (1st January 2015) - Neal, Clive R.; Donohue, Patrick; Fagan, Amy L.; O'Sullivan, Katie; Oshrin, Jocelyn; Roberts, Sarah
Abstract: Impact processes play an important role in shaping and reshaping the surfaces of airless planetary bodies. Such processes produce regoliths and generate melts that crystallize and record the homogenization of the geology at the impact site. If the volume of melt is substantial, the resultant crystallized product has an igneous texture and may be free of xenolithic clasts making it difficult to distinguish from melts produced by endogenic magmatic processes. This has been clearly demonstrated during the return of the Apollo samples from the Moon, where Apollo 14 basalt 14310 was initially described as a mare basalt and was only subsequently reclassified as an impact melt following detailed and time consuming crystallization experiments. Another way of distinguishing lunar impact melts from endogenically-derived mare basalts is through the quantification of the highly siderophile elements (HSE: Pd, Rh, Ru, Ir, Pt, Os), which have relatively low abundances in pristine lunar samples but are high in meteorites and, therefore, may be enriched in impact melts. However, these analyses consume relatively large quantities of valuable sample and because of mass constraints cannot be performed on many lunar samples. In this paper we present a quantitative petrographic method that has the potential to distinguish lunar impact melts from endogenically-derived mare basalts using plagioclase and olivine crystal size distributions (CSDs). The slopes and intercepts of these CSDs are used to show that olivine from impact melts displays a steeper CSD relative to olivine from mare basalts. For plagioclase, generally impacts melts display CSDs with shallower gradients than those from endogenous mare basalts and, as for olivines, plot in a distinct field on a CSD slope vs. CSD intercept plot. Using just a thin section to distinguish impact melts from mare basalts enables the goals of future robotic sample return missions to determine the age of the South Pole-Aitken basin in the Moon, because such missions will potentially only return small (2–4 mm) "rocklets" for analysis, obviating HSE analyses for impact melt identification.